(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The shoulder, being the most mobile joint in the body, is highly susceptible to dislocation, with anterior dislocation occurring most frequently. While most anterior dislocations are reducible through closed methods, which if left untreated, these may progress to an irreducible state. Irreducible cases are rare and pose significant diagnostic and therapeutic challenges, which often require surgical intervention. This case study highlights the non-invasive Ayurvedic management in an irreducible anterior shoulder dislocation in a 72year old female, following a fall. She was undiagnosed with shoulder dislocation and failed to immobilise for few weeks. Later imaging revealed anterior shoulder joint dislocation. Initial attempts at closed reduction were unsuccessful. After the non-invasive management of three weeks, dislocation was corrected with significant improvement. This case underscores the importance of recognizing irreducibility early, and the potential of Ayurvedic interventions in providing a non- invasive alternative for irreducible shoulder dislocations especially in geriatric patients where surgery may not be feasible.